ANALISA PENGARUH INFORMATIONAL FACTOR DAN IMAGE FACTOR PADA SHOW WINDOW TERHADAP PURCHASE INTENTION DENGAN FEEL GOOD FACTOR SEBAGAI VARIABLE INTERVENING PADA KONSUMEN WANITA ZARA WOMEN PAKUWON MALL SURABAYA - Regina Novembra Nau (Jurnal Strategi Pemasaran, 2019)
Today the retail industry in the world is rapidly growing retail, but one of the industries that is growing rapidly is retail fashion, one of which is the popular retail fashion, Zara. This phenomenon has a tremendous impact on consumer consumption patterns, the influence of emotional factors in the process of purchasing decisions and triggers can come from the attributes of a retail store, namely visual merchandising. And one of the visual merchandising categories is show window, there are 2 factors that represent the show window, namely informational factor and image factor. From this study the authors found that the informational factor and image factor on purchase intention with a good factor as an intervening variable for female consumers of Zara Women Pakuwon Mall Surabaya showed that informational factors affecting Zara Women female consumers turned out to have significant results when there was an intervening of good factor. However, the intervening of the feel good factor does not affect the relationship of image factor with purchase intention either directly or indirectly.